Environmental Management System (EMS) for military activities - strategies and policies of American, Canadian, Brazilian and NATO armies - Ferro, Marco Aurelio Chaves; Santos, Marilene de Oliveira Ramos Murias dos (Coleção Meira Mattos: revista das ciências militares, 2012)
Increasing of demand from environmental legislation and public opinion have transformed militaries activities, employees and facilities of Armed Forces all over the world. It became necessary to implement an Environmental Management System (EMS) to guide people how to participate on those activities even during peace or war times. It’s a common threat among all the armies that military planning documents nowadays have to consider the risks of damaging the environment which can be caused by military operations. This has led to a progressive updated of environmental military legislation in order to be in according to Federal Environmental Laws in each country. Military operations and training activities can have negative impacts on ecosystems due to the nature of the land use often result from damage to vegetation, digging activities, and soil disturbance from heavy troop traffic. Soil disturbance and associated erosion and sedimentation problems can further aggravate the ecological impacts of military land use on the ecosystems. The military’s essential mission is to win the war through the application of combat power warfare, which is destructive to the environment. This damage is a consequence of combat. However, it is necessary to restrict the application of force. The actions must conform to the law of land warfare, those established or not conventions and agreements that protect ecosystems against dispensable suffering and facilitate the restoration of peace. Although operational requirements are priority, the integration of environmental considerations into all aspects of military activities is fundamental for maintaining the health and well-being of the troops and the local population, for preventing irreparable damage to sites with natural, cultural, historic and archeological importance which discredit or complicate the mission objectives. The purpose of this work is to analyze the Environmental Management Systems adopted by American, Canadian, Brazilian armies and NATO’s, considering only topics related to strategic and politic levels. In spite of the differences that exist among those military institutions, there are some common aspects which can be cited. Those armies represent countries or organization (NATO) that have a very important role to play in the modern world. Their troops have been spread out around the whole world, operating in Iraq and Afghanistan, participating in peacekeeping missions in other countries as Haiti, for example. A key element of this transformation in the armies is the implementation of an Environmental Management System (EMS) as a mission enabler.